Clinical and immunological features in patients with neuroimmune complications of COVID-19 during Omicron wave in China: a case series - Gong, Siyin; Deng, Bo; Yu, Hai; Zhang, Xiang; Yang, Wenbo; Chen, Xiangjun (Frontiers in Immunology, 2024)
PurposeThis study aimed to present clinical and immunological features in patients with neuroimmune complications of COVID-19 during Omicron wave in China.MethodsPatients with neuroimmune complications associated with COVID-19 were retrospectively analyzed in Huashan Hospital from December 2022 to April 2023, during the widespread prevalence of Omicron variants in China. Demographic information, symptoms, electrophysiological findings, cerebrospinal fluid(CSF) test results and immunological markers, Magnetic Resonance Imaging(MRI) characteristics, treatment strategies and outcomes of these patients were reviewed and analyzed.ResultsA total of 53 cases of neuroimmune complications were included, with 7 cases of non-immune complications taken as controls. Neuroimmune complications comprised: 7 cases of Guillain-Barre syndrome/chronic inflammatory demyelinating polyneuropathy, 11 cases of spinal meningitis/myelitis, 2 cases of neuromyelitis optica spectrum disorder, 2 cases of myelin oligodendrocyte glycoprotein antibody-associated disease, 1 case of acute disseminated encephalomyelitis, 10 cases of autoimmune encephalitis, 17 cases of other encephalopathy/encephalitis and 3 cases of cerebellitis. SARS-CoV-2 was only detected in the CSF sample of one neuroimmune complications patient. CSF-restricted oligoclonal bands were detected in 11.1% (5/45) of neuroimmune patients, but absent in non-immune cases (0.0%, 0/5). Autoantibody testing identified specific antibodies in 26.5%(13/49) of neuroimmune cases and 0.0% (0/5) of non-immune cases. Glucocorticoids or intravenous immunoglobulins were administered as first-line treatments for all neuroimmune cases (100%, 53/53), whereas only 42.8% (3/7) of non-immune cases received these therapies. A baseline modified Rankin scale (mRS) score of 3 or above was present in the majority of both neuroimmune cases (96.2%, 51/53) and non-immune cases (71.4%, 5/7). At the end of a follow-up period, independent functional outcomes at day-90 with an mRS score below two were observed in a significant proportion of both neuroimmune cases (77.4%, 41/53) and non-immune case(71.4%, 5/7).ConclusionThe manifestations of neuroimmune complications of COVID-19 are diverse and can manifest with severe neurological deficits early in the course of the disease. The detection of immunological markers (such as autoantibody and oligoclonal bands) and immunotherapies can help to improve the prognosis of COVID-19 related neuroimmune complications.